772 Re-examining the Role of Post-Operative ICU Admission for Patients Undergoing Elective Craniotomy: A Systematic Review. (April 2023) - Azad, Tej D.; Shah, Pavan P.; Kannapadi, Nivedha; Rincon Torroella, Jordina N.; Xia, Yuanxuan; Bernhardt, Lydia; Hansen, Landon John; Materi, Joshua; Raj, Divyaansh; Jackson, Christopher Mitchell; Mukherjee, Raj; Gallia, Gary L.; et al.
Abstract : INTRODUCTION: The standard-of-care for post-operative care following elective craniotomy has historically been intensive care unit (ICU) admission. However, recent literature interrogating complications and interventions during this post-operative ICU stay suggests that all patients may not require this level of care. Thus, hospitals began implementing non-ICU post-operative care pathways for elective craniotomy. METHODS: A systematic review of the PubMed database was performed following PRISMA guidelines from database inception through August 2021. Included studies were published in peer-reviewed journals, in English, and described outcomes for patients undergoing elective craniotomies without post-operative ICU care. Data regarding study design, patient characteristics, and post-operative care pathways was extracted independently by two authors. Quality and risk of bias were evaluated using the Oxford Centre for Evidence-Based Medicine Levels of Evidence tool and Risk Of Bias In Non-Randomized Studies—of Interventions tool, respectively. RESULTS: In total, 1, 131 unique papers were identified through the database search, with 27 meeting inclusion criteria. Included articles were published from 2001-2021 and included non-ICU inpatient care and same-day discharge pathways. Overall, the studies demonstrated that post-operative non-ICU care for elective craniotomies led to length of stay reduction ranging from 6 hours to 4 days and notable cost reductions. Across 13 studies, 53 of the 2, 469 (2.1%) patients intended for post-operative management in a non-ICU setting required subsequent care escalation. CONCLUSIONS: Overall, these studies suggest that non-ICU care pathways for appropriately selected post-craniotomy patients may represent a meaningful opportunity to improve care value. However, included studies varied greatly in patient selection, post-operative care protocol, and outcomes reporting. Standardization and multi-institutional collaboration are needed to draw definitive conclusions regarding non-ICU post-operative care for elective craniotomy.